Perioperative Identification of an Accessory Fissure of the Right Lung - Yannick Taverne; Gert-Jan Kleinrensink; Peter de Rooij (Case Reports in Pulmonology)
Anatomical variations of lungs are common in clinical practice; however, they are sometimes overlooked in routine imaging. Surgical anatomy of the lung is complex and many variations are known to occur. A defective pulmonary development gives rise to variations in lobes and fissures. Morphological presentation is of clinical importance and profound knowledge of the organogenesis and functional anatomy is imperative for the interpretation and evaluation of lung pathophysiology and subsequent surgical intervention. However, appreciating them on radiographs and CT scans is difficult and they are therefore often either not identified or completely misinterpreted. As presented in this case report, an accessory fissure separating the superior segment of the right lower lobe from its native lobe was seen perioperatively and could only retrospectively be defined on X-rays and CT scan. It is imperative to keep in mind that accessory fissures can be missed on imaging studies and thus can make the surgical procedure more challenging.